Brief Report: The Effects of a Weighted Blanket on Engagement for a Student With ASD. (March 2019) - Zimmerman, Kathleen N.; Ledford, Jennifer R.; Severini, Katherine E.
The effectiveness of a weighted blanket intervention and structured work boxes for improving engagement for a child with autism during math circle time in a general education kindergarten classroom were evaluated relative to baseline using an alternating treatments design. The structured work boxes resulted in higher levels of engagement, and the weighted blanket resulted in levels that were similar to or lower than baseline. Additional research is needed on sensory-based interventions; in the meantime, teachers should use evidence-based practices.